Comparative ultrasound study of gastric emptying between an isotonic solution and a nutritional supplement - Bisinotto, Flora Margarida Barra; Silveira, Luciano Alves Matias Da; Rossi, Tiago Caneu; Martins, Laura Bisinotto; Zago, Gustavo Palis; Mendonça, Mariana Andrade Lopes (Sociedade Brasileira de Anestesiologia, 2019)
AbstractBackground and objectives: Preoperative fasting may lead to undesirable effects in the surgical patient in whom there is a stimulus to ingesting clear liquids until 2 hours before anesthesia. The aim of this study was to evaluate the gastric emptying of two different solutions using ultrasound.Methods: In a prospective, randomized, blind study, 34 healthy volunteers ingested 200 mL of two solutions without residues in two steps: an isotonic solution with carbohydrates, electrolytes, osmolarity of 292 mOsm.L-1, and 36 kcal; and other nutritional supplementation with carbohydrates, proteins, electrolytes, osmolarity of 680 mO.L-1, and 300 kcal. After 2 hours, a gastric ultrasound was performed to assess the antrum area and gastric volume, and the relation of gastric volume to weight (vol.w-1), whose value above 1.5 mL.kg-1 was considered a risk for bronchoaspiration. A p-value <0.05 was considered statistically significant.Results: There was a significant difference between all parameters evaluated 2 hours after the ingestion of nutritional supplementation compared to fasting. The same occurred when the parameters between isotonic solution and nutritional supplementation were compared 2 hours after ingestion. Only one patient had vol.w-1 <1.5 mL.kg-1 2 hours after ingestion of nutritional supplementation; and only one had vol.w-1 >1.5 mL.kg-1 after ingestion of isotonic solution.Conclusion: This study demonstrated that gastric emptying of equal volumes of different solutions depends on their constitution. Those with high caloric and high osmolarity, and with proteins present, 2 hours after ingestion, increased the gastric volumes, which is compatible with the risk of gastric aspiration.

ResumoJustificativa e objetivos: O jejum pré-operatório pode levar a efeitos indesejáveis no paciente cirúrgico, em que há um estimulo à ingestão de líquidos sem resíduos até 2 horas antes da anestesia. O objetivo deste estudo foi avaliar o esvaziamento gástrico de duas soluções diferentes por meio da ultrassonografia.Métodos: Em um estudo prospectivo, randomizado, cego, 34 voluntários saudáveis ingeriram 200 mL de duas soluções sem resíduos, em duas etapas: uma solução isotônica com carboidratos, eletrólitos, osmolaridade de 292 mOsm.L-1 e 36 kcal; e outra suplementação nutricional, com carboidratos, proteínas, eletrólitos, osmolaridade de 680 mOs.L-1 e 300 kcal. Após 2 horas, fez-se ultrassonografia gástrica com avaliação da área do antro e volume gástrico e relação do volume gástrico sobre o peso (vol.p-1), cujo valor acima de 1,5 mL.kg-1 foi considerado risco para broncoaspiração. Considerou-se p< 0,05 como estatisticamente significativo.Resultados: Houve diferença significativa entre todos os parâmetros avaliados 2 horas após a ingestão de suplementação nutricional em relação ao jejum. O mesmo ocorreu quando foram comparados os parâmetros entre solução isotônica e suplementação nutricional 2 horas após a ingestão. Apenas um paciente apresentou vol.p-1< 1,5 mL.kg-1 2 horas após a ingestão de suplementação nutricional; e apenas um apresentou vol.p-1 > 1,5 mL.kg-1, após a ingestão de solução isotônica.Conclusão: Este estudo demonstrou que o esvaziamento gástrico de volumes iguais de diferentes soluções depende de sua constituição. Aqueles com alto valor calórico e alta osmolaridade, e com proteínas presentes, 2 horas após a ingestão, aumentaram os volumes gástricos, compatíveis com o risco de aspiração gástrica.
Estudo comparativo do esvaziamento gástrico entre uma solução isotônica e um suplemento nutricional por meio da ultrassonografia
Keywords: Bronchoaspiration; Gastric ultrasound; Preoperative fasting; Broncoaspiração; Ultrassonografia gástrica; Jejum pré-operatório